2024
DOI: 10.1146/annurev-publhealth-040617-013638
|View full text |Cite
|
Sign up to set email alerts
|

Problems and Prospects: Public Health Regulation of Dietary Supplements

Abstract: Dietary supplements are a global business worth more than US$100 billion annually. These supplements are taken by up to 50% of adults and perhaps one-third of children in economically advanced economies. Definitions of dietary supplements differ from country to country, and regulation is generally lax and often seems to be directed more toward promoting commerce than protecting public health. Supplements may directly cause toxic reactions or may interact with other supplements or pharmaceuticals. Some suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
90
0
6

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(126 citation statements)
references
References 91 publications
0
90
0
6
Order By: Relevance
“…In terms of marketing, nutraceuticals include a large number of different products packaged for specific groups by age, gender, physical conditions and activity level. The global market was valued at US$109 billion in 2015 and is projected to reach US$180 billion by 2020 [3].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of marketing, nutraceuticals include a large number of different products packaged for specific groups by age, gender, physical conditions and activity level. The global market was valued at US$109 billion in 2015 and is projected to reach US$180 billion by 2020 [3].…”
Section: Introductionmentioning
confidence: 99%
“…The herbal supplement industry is a growing enterprise, expected to amount to $104.78 billion dollars or more by 2025 [11,12], yet, a recent study revealed that up to 60% of herbal supplements have substituted ingredients not listed on their labels, some of which are harmful contaminants [8]. For both marketing advantage and ethical concerns, suppliers must ensure accurate identification of all ingredients in their products [9].…”
Section: Introductionmentioning
confidence: 99%
“…The use of dietary supplements (DS) is gaining popularity in many Western societies over the past decades (Binns et al 2018;Centers for Disease Control and Prevention 2011;Messerer et al 2001;Rock 2007). DS refer to vitamins, minerals, oils, herbs and other nutritive and non-nutritive products that are consumed as an addition to the normal diet (Australian Bureau of Statistics 2014).…”
Section: Introductionmentioning
confidence: 99%